2017
DOI: 10.1016/j.semcdb.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Development and stem cells of the esophagus

Abstract: The esophagus is derived from the anterior portion of the developmental intermediate foregut, a structure that also gives rise to other organs including the trachea, lung, and stomach. Genetic studies have shown that multiple signaling pathways (e.g. Bmp) and transcription factors (e.g. SOX2) are required for the separation of the esophagus from the neighboring respiratory system. Notably, some of these signaling pathways and transcription factors continue to play essential roles in the subsequent morphogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 83 publications
4
66
0
Order By: Relevance
“…The septum separates the tracheal tube and esophagus and generates the trachea ventrally and the esophagus dorsally. This tracheal–esophageal separation occurs at approximately 4–6 weeks of gestation in humans . The failure of this process results in various anomalies such as esophageal atresia with or without tracheoesophageal fistula (EA/TEF).…”
Section: How Does the Esophagus Evolve Into The Normal Human Adult Stmentioning
confidence: 99%
See 1 more Smart Citation
“…The septum separates the tracheal tube and esophagus and generates the trachea ventrally and the esophagus dorsally. This tracheal–esophageal separation occurs at approximately 4–6 weeks of gestation in humans . The failure of this process results in various anomalies such as esophageal atresia with or without tracheoesophageal fistula (EA/TEF).…”
Section: How Does the Esophagus Evolve Into The Normal Human Adult Stmentioning
confidence: 99%
“…Similarly, downregulation of Sox2 in the early foregut leads to EA/TEF . The functions of Sox2 and Nkx2.1 are regulated by several signaling pathways . WNT/β‐catenin signaling pathway plays a crucial role in specifying Nkx2.1 + respiratory endoderm progenitors during development.…”
Section: How Does the Esophagus Evolve Into The Normal Human Adult Stmentioning
confidence: 99%
“…We also confirmed the reduction in the number of Sox2+ cells, and the effects produced by the partial depletion in tissues previously described as dependent on the activity of stem and progenitor Sox2+ cells. We inspected the testis (Arnold et al, 2011), esophagus and trachea (Zhang et al, 2017) and found that GCV‐treated mice were showing atrophic seminiferous tubules (Figure S2), a feature previously described for these transgenic mice after acute depletion of Sox2+ cells (Arnold et al, 2011) and a frequent event during aging (Gosden, Richardson, Brown, & Davidson, 1982), and a decreased epithelial cellularity in esophagus and trachea that corresponded with a reduced number of Sox2+ cells (Figure S2). …”
Section: Introduction Results Discussionmentioning
confidence: 99%
“…Around embryonic days 9.5-11.0, live imaging reveals a saddle-like structure that separates esophagus and stomach from trachea and lung. 47 Genetic models suggest that transcription factors (eg, SOX2, NKX2.1) and signaling molecules (eg, Noggin, Wnt2/2b) are critical for establishing esophagus from foregut, 48 after which esophageal lining changes from columnar into squamous epithelium under control of transcription factors like p63 and SOX2. A p63 gene deletion prevents this epithelial change, and SOX2 down-regulation causes esophageal progenitor cells to differentiate abnormally into mucin-secreting cells.…”
Section: Potential Origins Of Metaplasia In the Esophagus And Stomachmentioning
confidence: 99%
“…A p63 gene deletion prevents this epithelial change, and SOX2 down-regulation causes esophageal progenitor cells to differentiate abnormally into mucin-secreting cells. 48,49 Bmp signaling in the esophagus also is required for normal development of squamous epithelium. 50 In the stomach, multiple signaling pathways (eg, Bmp, Notch, Wnt) and transcription factors (eg, BARX1, NKX2.5, and GATA3) mediate the development of gastric glandular epithelia.…”
Section: Potential Origins Of Metaplasia In the Esophagus And Stomachmentioning
confidence: 99%